A kind of all-solid-state negative hydrogen ion battery
By reacting and combining the amino compounds, nitrides and hydrides of alkaline earth metals and rare earth metals under mild conditions, five-membered barium lanthanum oxynitride hydrides as hydrogen negative ion solid conductors, the shortcomings in the synthesis of multi-anion hydrides and hydrogen negative ion conduction research are solved, and the performance of efficient hydrogen negative ion batteries is achieved.
Patent Information
- Application Number
- CN202411905174.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-23
AI Technical Summary
There are few studies on the synthesis of multi-anion hydrides under mild conditions in the prior art and hydrogen negative ion conduction, and further research is still needed to adjust the synthesis conditions to regulate the composition and structure of solid electrolytes to achieve rapid hydrogen negative ion conduction.
By reacting and combining alkaline earth metal amino compounds, nitrides, hydrides with rare earth metal amino compounds, nitrides, and hydrides in hydrogen and oxygen-containing atmosphere, five-membered barium lanthanum oxynitride hydrides as hydrogen negative ion solid conductors. The chemical formula of the conductor is M1αM2βOxNyHz and is prepared by mechanical ball milling and calcining processes.
A multi-anionic hydride with H-ion conductivity >10-4S/cm and H-ion migration number >0.99 is achieved at above 100°C. It is used in all-solid hydrogen anionic battery, with excellent battery performance and simple and feasible preparation process.
Smart Images

Figure CN119340509B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an all-solid-state negative hydrogen ion battery, belonging to the field of negative hydrogen ion conductors. Background Art
[0002] All-solid-state batteries have been one of the hot topics in the field of energy research in recent years. Compared with traditional liquid electrolyte batteries, all-solid-state batteries use solid electrolytes, which can effectively avoid the leakage and combustion problems of liquid electrolytes and significantly improve the safety of batteries. At present, the research on all-solid-state battery technology mainly focuses on lithium, sodium, and potassium ion conductors, while research on hydrogen anion conductors is very rare. - / H 2 Due to their high redox potential (-2.3 V) and high energy density, electrochemical devices based on hydrogen anion conductors are expected to revolutionize energy storage and conversion technologies.
[0003] Regarding hydrogen anion conductors, they can be roughly divided into metal hydrides and polyanion hydrides. For metal hydrides, researchers discovered in the last century that vacancies have an important influence on the electrical properties of such compounds. Calcium hydride and strontium hydride doped with trace amounts of Na elements show significant hydrogen conductivity. The introduction of H vacancies not only increases the carrier concentration, but also effectively inhibits electronic conduction [GIPanov., React.Kinet.Gatal. ,1985,29,443-450.]. Later in BaH 2 The study found that BaH 2 At high temperatures, a reversible phase transition occurs, during which one of the H sites splits, resulting in a decrease in H occupancy by nearly half. - The migration ability of ions is greatly increased, BaH 2 The ionic conductivity is significantly higher than that of many typical proton or O 2- Ionic Conductors [John T. S. Irvine, Nat. Mater. , 2015, 14, 95-100.]. In 2023, Chen et al. reported a strategy that can effectively suppress the electronic conductivity of materials through ball milling process, making LaH x Becoming a hydrogen-negative superion conductor has promoted the development and application of hydrogen-negative ion batteries [Chen, Nature , 2023, 616, 73-76.]. For polyanionic hydrides, it is a relatively reasonable synthetic strategy to regulate the structure and ion conduction of metal hydrides by introducing multiple anions. The main research interests of polyanionic hydrides are concentrated on oxygen hydrides or nitrogen hydrides. In 2016, the first report of H - Ions, O 2-Ions and various highly electropositive metal elements form a stable layered perovskite structure, in which Sr and La of different valence states occupy the same lattice site. By adjusting the content of Sr, the H - The vacancy concentration of ions, in turn, affects the ion conductivity of the material [G. Kobayashi, Science , 2016, 351, 1314-1317.]. Hosono et al. found that in LaH 3 O doping in the form of LaH 3- 2x O x , which can effectively suppress electronic conductivity and meet the basic requirements as a solid electrolyte [H.Hosono, J.Am.Chem.Soc. , 2022, 144, 1523.]. These polyanion hydrides are usually synthesized at high temperature and high pressure or at high pressure in multi-anvils, so the synthesis conditions are very harsh [Kageyama, Nat. Commun. , 2018, 9, 772.]. However, there are few reports on the synthesis of polyanionic hydrides under mild conditions. Therefore, developing a strategy to synthesize polyanionic hydrides under mild conditions is very important for the study of hydrogen anion conduction.
[0004] If nitrogen and oxygen can be introduced into metal hydrides so that the material contains three anions, a special oxynitride hydride will be formed. For oxynitride hydrides, only one research result has been reported. The researchers synthesized BaCeO at 300℃-900℃. x N y H z , and studied its crystal structure and catalytic activity for ammonia synthesis [H.Hosono, J.Am.Chem.Soc ., 2019, 141, 51, 20344–20353.]. However, the hydrogen ion conductivity of this material has not been studied.
[0005] In summary, there is still little research on the synthesis of polyanionic hydrides under mild conditions and the conduction of hydrogen anions. The mechanism of hydrogen anion conduction and the action of various anions is still unclear. How to adjust the composition and structure of solid electrolytes by adjusting the synthesis conditions to achieve fast hydrogen anion conduction still requires further research. Summary of the invention
[0006] Alkaline earth metal and rare earth metal hydrides, such as strontium hydride, barium hydride, lanthanum hydride, etc., are a class of solid electrolyte materials with fast hydride ion conduction. Lanthanum hydride can effectively suppress electronic conductivity through simple ball milling, so that it can be assembled into a solid-state hydride battery for discharge testing.
[0007] On this basis, the applicant has discovered that alkaline earth metal amides, nitrides, hydrides and rare earth metal amides, nitrides, hydrides can react and combine in a hydrogen and oxygen-containing atmosphere to form pentavalent barium lanthanum oxynitrogen hydride.
[0008] According to one aspect of the present application, an all-solid-state negative hydride ion battery is provided, comprising a positive electrode containing a negative hydride ion donor, a negative electrode capable of storing negative hydride ions, and a negative hydride ion solid-state conductor between the positive electrode and the negative electrode.
[0009] The chemical formula of the hydrogen anion solid conductor is M 1 α M 2 β O x N y H z .
[0010] Among them, M 1 At least one selected from the group consisting of alkaline earth metal elements Ba, Sr, Ca, and Mg.
[0011] M 2 At least one selected from the lanthanide metal elements La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.
[0012] 0≤α≤6, 0≤β≤4, and α and β are not 0 at the same time.
[0013] 0 <x≤6,0<y≤4,0<z≤12。
[0014] When M 2 When it is trivalent, 2α+3β=2x+3y+z.
[0015] When M 2 When it is tetravalent, 2α+4β=2x+3y+z.
[0016] The hydrogen anion solid conductor is prepared by the following steps: 1 Source and M 2 The sources are mixed, mechanically ball-milled, calcined in a hydrogen atmosphere (I), and calcined in an oxygen atmosphere (II) to obtain the hydrogen anion solid conductor.
[0017] The M 1 Source: M 1 of nitrogen-containing compounds.
[0018] The M 2 Source: M 2 of nitrogen-containing compounds.
[0019] The M 1Source: Ba 3 N 2 , Sr 3 N 2 , Ca 3 N 2 Mg 3 N 2 、Ba(NH 2 ) 2 、Sr(NH 2 ) 2 , Ca(NH 2 ) 2 Mg(NH 2 ) 2 , BaNH, SrNH, CaNH, MgNH.
[0020] The M 2 Source selected from LaN, CeN, PrN, NdN, PmN, SmN, EuN, GdN, TbN, DyN, HoN, ErN, TmN, YbN, LuN, La(NH 2 ) 3 、Ce(NH 2 ) 3 、Pr(NH 2 ) 3 、Nd(NH 2 ) 3 、Pm(NH 2 ) 3 、Sm(NH 2 ) 3 Eu(NH 2 ) 3 、Gd(NH 2 ) 3 、Tb(NH 2 ) 3 、Dy(NH 2 ) 3 、Ho(NH 2 ) 3 、Er(NH 2 ) 3 、Tm(NH 2 ) 3 Yb(NH 2 ) 3 、Lu(NH 2 ) 3 ,La 2 (NH) 3 、Ce 2 (NH) 3 , Pr 2 (NH) 3 、Nd 2 (NH)3 、Pm 2 (NH) 3 、Sm 2 (NH) 3 、Eu 2 (NH) 3 , Gd 2 (NH) 3 , Tb 2 (NH) 3 、Dy 2 (NH) 3 、Ho 2 (NH) 3 , Er 2 (NH) 3 、Tm 2 (NH) 3 , Yb 2 (NH) 3 、Lu 2 (NH) 3 At least one of .
[0021] The rotation speed of the mechanical ball mill is 50-400 rpm.
[0022] Optionally, the rotation speed of the mechanical ball mill is any value of 50 rpm, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm or any range value between two of them.
[0023] The mechanical ball milling time is 1 to 48 hours.
[0024] Optionally, the time of the mechanical ball milling is any value among 1h, 2h, 4h, 6h, 8h, 12h, 24h, 36h, 48h, or a range between any two of them.
[0025] Optionally, the mechanical ball milling time is 6 to 24 hours.
[0026] The pressure of the hydrogen atmosphere is 0.1~3Mpa.
[0027] Optionally, the pressure of the hydrogen atmosphere is any value among 0.1 MPa, 0.5 MPa, 1 MPa, 2 MPa, 3 MPa, or a range between any two values.
[0028] The temperature of the calcination I is 100-500°C.
[0029] Optionally, the calcination temperature I is any value of 100°C, 200°C, 300°C, 400°C, 500°C, or a range between any two of them.
[0030] The calcination time is 1 to 96 hours.
[0031] Optionally, the calcination time I is any value among 1h, 2h, 4h, 8h, 12h, 24h, 36h, 48h, 60h, 72h, 84h, 96h, or a range value between any two of them.
[0032] Optionally, the calcination time is 2 to 24 hours.
[0033] The oxygen-containing atmosphere consists of oxygen and inert gas, wherein the volume fraction of oxygen is 1-50%.
[0034] Optionally, the volume fraction of oxygen is any value of 1%, 10%, 20%, 30%, 40%, 50%, or a range between any two of them.
[0035] The pressure of the oxygen-containing atmosphere is 0.1~1Mpa.
[0036] Optionally, the pressure of the oxygen-containing atmosphere is any value among 0.1 MPa, 0.5 MPa, 1 MPa, or any range between the two.
[0037] The temperature of the calcination II is 100-600°C.
[0038] Optionally, the calcination temperature II is any value of 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, or a range between any two of them.
[0039] The calcination time II is 1 to 24 hours.
[0040] Optionally, the calcination time II is any value among 1h, 2h, 4h, 6h, 8h, 12h, 20h, 24h, or a range between any two of them.
[0041] Optionally, the calcination time II is 2 to 8 hours.
[0042] When the hydrogen negative ion solid conductor is above 100°C, H - Ionic conductivity>10 -4 S / cm,H - Ion mobility > 0.99.
[0043] The beneficial effects of this application include:
[0044] 1) This application provides a new polyanion hydride that can be used as a hydrogen anion solid conductor. - Ionic conductivity>10 -4 S / cm,H - Ion mobility > 0.99.
[0045] 2) The polyanion hydride provided in this application can be used in all-solid-state hydrogen-ion batteries and has excellent battery performance.
[0046] 3) The polyanion hydride provided in this application has a simple preparation process and can be actually used in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 Ba(NH 2 ) 2 、La(NH 2 ) 3 Argon temperature programmed desorption mass spectrum.
[0048] Figure 2 For Ba 3 La 2 O 4.4 N 0.81 H 0.77 Argon temperature programmed desorption mass spectrum.
[0049] Figure 3 For Ba 3 La 2 O 4.4 N 0.81 H 0.77 The powder XRD patterns of Ba(NH 2 ) 2 、La(NH 2 ) 3 for comparison.
[0050] Figure 4 For Ba 3 La 2 O 4.4 N 0.81 H 0.77 Pawley fitting spectrum.
[0051] Figure 5 This is the hydrogen ion conductivity of the five-element barium lanthanum oxynitrogen hydride obtained in Example 2.
[0052] Figure 6 Ba 3 La 2 O 4.4 N 0.81 H 0.77 Discharge performance of all-solid-state batteries assembled with hydrogen anion solid electrolyte. DETAILED DESCRIPTION
[0053] To further illustrate the present invention, the following specific examples are listed, but they do not limit the scope of the invention defined by the appended claims.
[0054] Example 1
[0055] In an argon glove box, accurately weigh barium amide (Ba(NH 2 ) 2 )0.563g and lanthanum amino (La(NH 2 ) 3 ) 0.414 g, placed in a stainless steel ball mill, added 1 MPa of ammonia, ball milled on a planetary ball mill at 200 rpm for 20 h, heated at 350 ° C for 10 h under hydrogen, and then heated in 0.4 MPa of 20% O 2 Ba was obtained by calcining at 450℃ for 3h under / Ar 3 La 2 O 4.4 N 0.81 H 0.77 .
[0056] like Figure 1 , 2 The figure shows the argon temperature-programmed desorption mass spectrum of the five-element barium lanthanum oxynitrogen hydride. It can be seen that the decomposition behavior of this substance is completely different from that of barium amide and lanthanum amide. The two amino compounds release ammonia in the low temperature region, while the five-element barium lanthanum oxynitrogen hydride only releases hydrogen but no ammonia, indicating that the five-element barium lanthanum oxynitrogen hydride is a relatively stable polyanion hydride. The precursor is heated to 20% O at 0.4 MPa. 2 The composition of the sample calcined under the mixed gas of Ba / Ar is 3 La 2 O 4.4 N 0.81 H 0.77 .
[0057] XRD spectrum Figure 3 As shown in the figure, Ba 3 La 2 O 4.4 N 0.81 H 0.77 The diffraction peaks of are completely different from those of the two amino compounds, and the Pawley simulation ( Figure 4 ) can be determined to be a Pnma A new substance with a crystal group configuration belongs to the orthorhombic crystal structure.
[0058] In an argon glove box, accurately weigh Ba 3 La 2 O 4.4 N 0.81 H 0.7780mg, pressed into a disc with a thickness of 1mm and a diameter of 5mm, and placed in a homemade test tube. The sample was heated between 300℃ and 420℃, and the conductivity of the sample was tested by electrochemical impedance spectroscopy and DC polarization method. The test results are as follows Figure 5 As shown in Figure 2, at 420°C, the ionic conductivity of the sample is as high as 2.52×10 -2 S / cm, the ion migration number is 0.993, and the ionic conductivity of the material is the best among the known reported hydrogen anion conductors in the high temperature region.
[0059] In an argon glove box, accurately weigh Ba 3 La 2 O 4.4 N 0.81 H 0.77 120mg as electrolyte for hydrogen anion solid-state battery, accurately weigh 12mgTiH 2 , 1mg carbon powder, 10mgBa 3 La 2 O 4.4 N 0.81 H 0.77 After grinding and mixing, as the battery anode, accurately weigh 2.5mgTi, 1mg carbon powder, 10mgBa 3 La 2 O 4.4 N 0.81 H 0.77 After grinding and mixing, it is used as the battery cathode and assembled into a sandwich structure hydrogen anion solid-state battery. The battery discharge curve of the test battery at 400°C is as follows Figure 6 As shown in Figure 2, the battery has an open circuit voltage of 265 mV at 400 °C and a discharge capacity of up to 467 mAh g -1 .
[0060] Example 2
[0061] In an argon glove box, accurately weigh barium amide (Ba(NH 2 ) 2 )0.563g and lanthanum amino (La(NH 2 ) 3 ) 0.414 g was placed in a stainless steel ball mill, 1 MPa of ammonia was added, and the mixture was ball milled at 200 rpm for 20 h on a planetary ball mill. The reactants were heated at 350 °C for 10 h under hydrogen, and then heated at 0.1, 0.2, 0.6 or 0.8 MPa of 20% O 2 / Ar and calcined at 450°C for 3h to obtain pentavalent barium lanthanum oxynitrides of other compositions.
[0062] In an argon glove box, 80 mg of each of the four samples were accurately weighed, pressed into discs with a thickness of 1 mm and a diameter of 5 mm, and placed in a homemade test tube. The samples were heated between 300°C and 420°C, and the conductivity of the samples was tested using electrochemical impedance spectroscopy and DC polarization. The test results are shown in Figure 2. Figure 5 shown.
[0063] Example 3
[0064] In an argon glove box, accurately weigh strontium amine (Sr(NH 2 ) 2 )0.399g and lanthanum amino (La(NH 2 ) 3 ) 0.414 g was placed in a stainless steel ball mill, 1 MPa of ammonia was added, and the mixture was ball milled at 50 rpm for 40 h on a planetary ball mill. The reactants were heated at 500 °C for 4 h under hydrogen, and then heated at 0.1 MPa of 50% O 2 / Ar and calcined at 200°C for 20 h to obtain pentavalent strontium lanthanum oxynitride.
[0065] In an argon glove box, 80 mg of the sample was accurately weighed, pressed into a disc with a thickness of 1 mm and a diameter of 5 mm, and placed in a homemade test tube. The sample was heated between 300°C and 420°C, and the conductivity of the sample was tested by electrochemical impedance spectroscopy and DC polarization.
[0066] Example 4
[0067] In an argon glove box, accurately weigh barium amide (Ba(NH 2 ) 2 ) 0.612 g and aminocerium ((NH 2 ) 3 ) 0.453 g, placed in a stainless steel ball mill, added 1 MPa of ammonia, ball milled on a planetary ball mill at 400 rpm for 1 h, heated at 150 °C for 90 h under hydrogen, and then heated at 0.8 MPa of 20% O 2 / Ar and calcined at 550 °C for 8 h to obtain pentavalent barium cerium oxynitride.
[0068] In an argon glove box, 80 mg of the sample was accurately weighed, pressed into a disc with a thickness of 1 mm and a diameter of 5 mm, and placed in a homemade test tube. The sample was heated between 300°C and 420°C, and the conductivity of the sample was tested by electrochemical impedance spectroscopy and DC polarization.
[0069] Example 5
[0070] In an argon glove box, accurately weigh strontium amine (Sr(NH 2 ) 2 )0.434g and aminocerium (Ce(NH 2) 3 ) 0.453 g, placed in a stainless steel ball mill, added 1 MPa of ammonia, ball milled on a planetary ball mill at 200 rpm for 24 h, heated at 350 ° C for 24 h under hydrogen, and then heated at 0.4 MPa of 20% O 2 / Ar and calcined at 450°C for 3h to obtain pentavalent strontium cerium oxynitride with other compositions.
[0071] In an argon glove box, 80 mg of the sample was accurately weighed, pressed into a disc with a thickness of 1 mm and a diameter of 5 mm, and placed in a homemade test tube. The sample was heated between 300°C and 420°C, and the conductivity of the sample was tested by electrochemical impedance spectroscopy and DC polarization.
[0072] Example 6
[0073] In an argon glove box, accurately weigh barium amide (Ba(NH 2 ) 2 )0.609g and praseodymium amine (Pr(NH 2 ) 3 ) 0.453 g, placed in a stainless steel ball mill, added 1 MPa of ammonia, ball milled on a planetary ball mill at 200 rpm for 20 h, heated at 350 ° C for 10 h under hydrogen, and then heated in 20% O at 0.4 MPa. 2 / Ar and calcined at 450°C for 3h to obtain pentavalent barium praseodymium oxynitride with other compositions.
[0074] In an argon glove box, 80 mg of the sample was accurately weighed, pressed into a disc with a thickness of 1 mm and a diameter of 5 mm, and placed in a homemade test tube. The sample was heated between 300°C and 420°C, and the conductivity of the sample was tested by electrochemical impedance spectroscopy and DC polarization.
[0075] Example 7
[0076] In an argon glove box, accurately weigh strontium amine (Sr(NH 2 ) 2 )0.431g and praseodymium amine (Pr(NH 2 ) 3 ) 0.453 g, placed in a stainless steel ball mill, added 1 MPa of ammonia, ball milled on a planetary ball mill at 200 rpm for 20 h, heated at 350 ° C for 10 h under hydrogen, and then heated in 20% O at 0.4 MPa. 2 / Ar and calcined at 450°C for 3h to obtain pentavalent strontium praseodymium oxynitrides of other compositions.
[0077] In an argon glove box, 80 mg of the sample was accurately weighed, pressed into a disc with a thickness of 1 mm and a diameter of 5 mm, and placed in a homemade test tube. The sample was heated between 300°C and 420°C, and the conductivity of the sample was tested by electrochemical impedance spectroscopy and DC polarization.
[0078] Example 8
[0079] In an argon glove box, calcium amide (Ca(NH 2 ) 2 )0.262g and lanthanum amino (La(NH 2 ) 3 ) 0.453 g, placed in a stainless steel ball mill, added 1 MPa of ammonia, ball milled on a planetary ball mill at 200 rpm for 20 h, heated at 350 ° C for 10 h under hydrogen, and then heated in 20% O at 0.4 MPa. 2 / Ar and calcined at 450°C for 3h to obtain pentavalent calcium lanthanum oxynitrides of other compositions.
[0080] In an argon glove box, 80 mg of the sample was accurately weighed, pressed into a disc with a thickness of 1 mm and a diameter of 5 mm, and placed in a homemade test tube. The sample was heated between 300°C and 420°C, and the conductivity of the sample was tested by electrochemical impedance spectroscopy and DC polarization.
[0081] Example 9
[0082] In an argon glove box, calcium amide (Ca(NH 2 ) 2 )0.26g and aminocerium (Ce(NH 2 ) 3 ) 0.453 g, placed in a stainless steel ball mill, added 1 MPa of ammonia, ball milled on a planetary ball mill at 200 rpm for 20 h, heated at 350 ° C for 10 h under hydrogen, and then heated in 20% O at 0.4 MPa. 2 / Ar and calcined at 450°C for 3h to obtain pentavalent calcium cerium oxynitrides of other compositions.
[0083] In an argon glove box, 80 mg of the sample was accurately weighed, pressed into a disc with a thickness of 1 mm and a diameter of 5 mm, and placed in a homemade test tube. The sample was heated between 300°C and 420°C, and the conductivity of the sample was tested by electrochemical impedance spectroscopy and DC polarization.
[0084] Example 10
[0085] In an argon glove box, calcium amide (Ca(NH 2 ) 2 )0.259g and praseodymium amine (Pr(NH 2 )3 ) 0.453 g, placed in a stainless steel ball mill, added 1 MPa of ammonia, ball milled on a planetary ball mill at 200 rpm for 20 h, heated at 350 ° C for 10 h under hydrogen, and then heated in 20% O at 0.4 MPa. 2 / Ar and calcined at 450°C for 3h to obtain pentavalent calcium praseodymium oxynitrides of other compositions.
[0086] In an argon glove box, 80 mg of sample was accurately weighed, pressed into a disc with a thickness of 1 mm and a diameter of 5 mm, and placed in a homemade test tube. The sample was heated between 300°C and 420°C, and the conductivity of the sample was tested by electrochemical impedance spectroscopy and DC polarization method.
[0087] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. An all-solid-state negative hydrogen ion battery, characterized in that: The invention comprises a positive electrode including a hydride negative ion donor, a negative electrode capable of storing hydride negative ions, and a hydride negative ion solid conductor between the positive electrode and the negative electrode; The chemical formula of the hydrogen anion solid conductor is M 1 α M 2 β O x N y H z ; Among them, M 1 At least one selected from the group consisting of alkaline earth metal elements Ba, Sr, Ca, and Mg; M 2 At least one selected from the group consisting of lanthanide metal elements La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; 0≤α≤6, 0≤β≤4, and α and β are not 0 at the same time; 0 <x≤6,0<y≤4,0<z≤12; When M 2 When it is trivalent, 2α+3β=2x+3y+z; When M 2 When it is tetravalent, 2α+4β=2x+3y+z.
2. The all-solid-state negative hydrogen ion battery according to claim 1, characterized in that: The negative hydrogen ion solid conductor is prepared by the following steps: M 1 Source and M 2 The sources are mixed, mechanically ball-milled, calcined in a hydrogen atmosphere (I), and calcined in an oxygen atmosphere (II) to obtain the hydrogen anion solid conductor.
3. The all-solid-state negative hydrogen ion battery according to claim 2, characterized in that: The M 1 Source: M 1 nitrogen-containing compounds; The M 2 Source: M 2 of nitrogen-containing compounds.
4. The all-solid-state negative hydrogen ion battery according to claim 2, characterized in that: The M 1 The source is selected from at least one of Ba3N2, Sr3N2, Ca3N2, Mg3N2, Ba(NH2)2, Sr(NH2)2, Ca(NH2)2, Mg(NH2)2, BaNH, SrNH, CaNH, and MgNH; The M 2 The source is selected from LaN, CeN, PrN, NdN, PmN, SmN, EuN, GdN, TbN, DyN, HoN, ErN, TmN, YbN, LuN, La(NH2)3, Ce(NH2)3, Pr( NH2)3, Nd(NH2)3, Pm(NH2)3, Sm(NH2)3, Eu(NH2)3, Gd(NH2)3, Tb(NH2)3, Dy(NH2)3, Ho(NH2)3, Er(NH2) 3, at least one of Tm(NH2)3, Yb(NH2)3, Lu(NH2)3, La2(NH)3, Ce2(NH)3, Pr2(NH)3, Nd2(NH)3, Pm2(NH)3, Sm2(NH)3, Eu2(NH)3, Gd2(NH)3, Tb2(NH)3, Dy2(NH)3, Ho2(NH)3, Er2(NH)3, Tm2(NH)3, Yb2(NH)3, and Lu2(NH)3.
5. The all-solid-state negative hydrogen ion battery according to claim 2, characterized in that: The rotation speed of the mechanical ball mill is 50-400 rpm; The mechanical ball milling time is 1 to 48 hours; The pressure of the hydrogen atmosphere is 0.1~3Mpa; The temperature of the calcination I is 100-500° C.; The calcination time is 1 to 96 hours.
6. The all-solid-state negative hydrogen ion battery according to claim 2, characterized in that The mechanical ball milling time is 6 to 24 hours.
7. The all-solid-state negative hydrogen ion battery according to claim 2, characterized in that: The time of the calcination is 2 to 24 hours.
8. The all-solid-state negative hydrogen ion battery according to claim 2, characterized in that: The oxygen-containing atmosphere is composed of oxygen and inert gas, wherein the volume fraction of oxygen is 1-50%; The pressure of the oxygen-containing atmosphere is 0.1~1Mpa; The temperature of the calcination II is 100-600°C; The calcination time II is 1 to 24 hours.
9. The all-solid-state negative hydrogen ion battery according to claim 2, characterized in that: The calcination time II is 2 to 8 hours.
10. The all-solid-state negative hydrogen ion battery according to claim 1, characterized in that: When the hydrogen negative ion solid conductor is above 100°C, H - Ionic conductivity>10 -4 S / cm,H - Ion mobility > 0.99.
Citation Information
Patent Citations
Lithium ion battery solid electrolyte material
CN106981682A
Hydrogen anion conductor and preparation method and application thereof
CN117995456A
Cited By
A hydrogen ion battery based on titanium negative electrode and preparation method thereof
CN120413820B